The Influence of Carbon Emission Disclosure, Corporate Social Responsibility, and Corporate Governance on Firm Value with Financial Flexibility as a Moderating Variable in the SRI-KEHATI Index - Dita Fatimah Khairani; Isfenti Sadalia; Syahyunan (Journal of Business Management, 2026)
This study aims to analyze the effect of carbon emission disclosure, corporate social responsibility, and corporate governance on company value in the SRI-KEHATI Index during the period 2019-2023. In addition, this study also examines financial flexibility as a moderating variable in the relationship between carbon emission coverage, corporate social responsibility, and corporate governance. The research sample was determined using a purposive sampling technique, resulting in 19 companies as research samples. The analytical method used in this study is Moderate Regression Analysis (MRA). The results show that carbon emission disclosure has a negative and insignificant effect on company value, corporate social responsibility has a positive and insignificant effect on company value, and corporate governance has a positive and insignificant effect on company value. In addition, financial flexibility moderates the effect of carbon emission disclosure on company value positively and significantly. Other results show that financial flexibility moderates the effect of carbon emitting disclosure on company value positively and significantly, and moderates the effect of corporate governance on company value positively but not significantly. These findings provide an important contribution to the literature on the factors determining firm value, particularly for companies included in the SRI-KEHATI Index. They also provide a basis for management in developing strategies for freezing and unfreezing financial statements to enhance firm value.